Development of eDNA methods for monitoring two stygobiotic species of the Dinaric Karst, Proteus anguinus and Congeria jalzici, using digital PCR - Špela Gorički; Primož Presetnik; Uršula Prosenc-Zmrzljak; Tajda Gredar; Matej Blatnik; Blaž Kogovšek; Oliver Koit; Cyril Mayaud; Sara Strah; Branko Jalžić; Gregor Aljančič; Dejan Štebih; et al. (Natura Sloveniae)
n/a